Intestinal Infarction and Portal Vein Thrombosis in a Patient with Henoch Schonlein Purpura - Mekdess Abebe; Asha Patnaik; Frederick Miller; Heidi Roppelt; Nand K. Wadhwa; Mersema Abate; Edward P. Nord (Case Reports in Rheumatology)
Henoch Schonlein purpura is a systemic vasculitis that commonly affects children and teenagers but also affects adults of all ages. In most instances it has a benign course. Organ involvement, particularly in adults, and notably the kidneys and gastrointestinal tract may require therapeutic intervention and may have a less favorable outcome. We report a case of a 58-year-old man who presented with purpura and who rapidly developed catastrophic intestinal vasculitis, leading to his demise.